An Examination of the Role of Mentees' Social Skills and Relationship Quality in a School‐Based Mentoring Program. Issue 1 (25th September 2019) - Schenk, Loïs; Sentse, Miranda; Lenkens, Margriet; Nagelhout, Gera E.; Engbersen, Godfried; Severiens, Sabine
Abstract: Research on youth mentoring highlights the importance of the relationship quality between mentor and mentee; mentoring results in more positive outcomes when the mentee perceives the relationship as satisfying and trustworthy. Research on relationship quality shows that social skills are important for constructing new relationships. However, whereas improved social skills are often one of the main goals of youth mentoring, little is known about the importance of social skills for relationship quality in youth mentoring relations. In this study, we examined whether mentee's pre‐intervention social skills were related to mentor–mentee relationship quality as perceived by the mentee, and in turn, if relationship quality was associated with post‐intervention social skills. We additionally examined possible gender and age differences in these associations. Data were used from a two‐wave study that assessed relationship quality and social skills before and after one semester of mentoring of 390 secondary school students in a school‐based mentoring program. Results indicated that relationship quality was positively associated with post‐intervention social skills. However, only for young mentees pre‐intervention social skills were associated with better relationship quality. Moreover, only for young mentees, relationship quality mediated the association between pre‐ and post‐intervention social skills. Highlights: Mentees' perceived relationship quality is positively associated to social skill outcomes. Young mentees' pre‐social skills are positively associated to mentor‐mentee relationship quality. Relationship quality only mediates young mentees' pre and post‐social skills. Relationship quality is equally important for boys and girls in changes in social skills.